State of the Art of Low‐Frequency Acoustic Modulation: Intensity Enhancement and Directional Control - Jingsong Xu; Yunfeng Ye; Tao Dong; Zhaochu Yang; Nuno Miguel Matos Pires; Yu Zhou; Fuyu Tao; Jin Wang; Junshan Zhang; Guoxi Luo; Libo Zhao; Qi Mao; et al. (Advanced Science)
Abstract High‐intensity low‐frequency acoustic sources with directivity play a significant role in various fields such as medical treatment, underwater communication, and environmental monitoring. However, the long wavelengths, strong penetration, and their tendency to easily diffract of low‐frequency acoustic waves make it challenging to achieve directional control and intensity enhancement. Thanks to the development of acoustic metamaterials, acoustic devices can now effectively manipulate low‐frequency acoustic waves at subwavelength scales with excellent acoustic performance. Currently, the directional control and intensity enhancement of low‐frequency acoustic waves mainly concentrate on source design and the modulation of propagation processes. These techniques employ acoustic resonance, focusing, and other phase control methods to achieve energy concentration and directional control of low‐frequency acoustic waves. Nevertheless, existing low‐frequency acoustic wave control techniques still face issues such as low energy efficiency, poor directional control, and limited controllable bandwidth. This paper systematically reviews methods for achieving high‐intensity emission and directional control of low‐frequency acoustic waves, comprehensively compares the advantages and disadvantages of various technologies, and discusses how to extend these methods to lower acoustic frequency bands, aiming to provide new insights for the development of miniaturized, efficient, and accurately directional ultra‐low frequency acoustic devices.